Cells containing factor XIIIa and pulmonary fibrosis induced by bleomycin. Issue 3 (March 1991) - Toida, M; Okumura, Y; Takami, T
Abstract : To show the clinical importance of cells containing FXIIIa in pulmonary fibrosis induced by bleomycin, the distributions of FXIIIa and collagenous components were investigated immunohistochemically in both normal lung tissues and those affected by bleomycin. In the normal tissues FXIIIa-containing cells were sparse, but they were numerous in the pulmonary fibrotic tissues, especially in the subpleural area and around the blood vessels of alveolar septa, where slight to moderate fibrosis was seen, and in the intra-alveolar fibrinous exudate. In the collagenous scar-like areas, however, these cells were fewer in number and their FXIIIa expression was depleted. These findings suggest that cells containing FXIIIa have an important role in the development of pulmonary fibrosis induced by bleomycin.